Synthesis of zirconium carbide via sol-gel method as a precursor for micro- and mesoporous carbide-derived carbon materials - Maarja Paalo; Selin Su Yegit; Lilian Moumaneix; Tanja Kallio; Alar Jänes (Carbon Trends)
The sol-gel method was used to synthesize a carbide precursor, which was then chlorinated to obtain micro- and mesoporous carbon material. Zirconium alkoxide was used as the starting material in the sol-gel synthesis process. The final carbon material was produced by chlorinating the sol-gel synthesized carbide at three different chlorination temperatures, 700 °C, 800 °C and 900 °C. Characterization of the synthesized carbide precursor and the final carbon materials revealed that all materials were porous. Sorption measurements were used to calculate specific surface areas using non-local density functional theory (NLDFT). The surface area of the sol-gel synthesized carbide reached up to 65 m2 g−1, while the carbon materials achieved surface areas up to 1570 m2 g−1. For comparison, carbide-derived carbon materials were also synthesized from commercial zirconium carbide. The commercial zirconium carbide has very low porosity, resulting in a final carbon material that was primarily microporous, with a specific NLDFT surface area similar to that of sol-gel synthesized carbide-derived carbon material. However, the key difference is that carbon materials derived from commercial zirconium carbide contained only micropores, whereas the sol-gel synthesized carbide-derived carbon also have mesoporous areas. This mesoporosity is crucial for applications such as rapid ion transport in supercapacitor electrodes.